ECOLOGICAL NOTES ON THE DIFFERENCES IN FLORA AND HABITAT OF LICHENS BETWEEN THE SYOWA STATION AREA IN CONTINENTAL ANTARCTIC AND KING GEORGE ISLAND IN MARITIME ANTARCTIC (Twelfth Symposium on Polar Biology) - イノウエ, マサカネ; INOUE, Masakane (National Institute of Polar Research, 1991)
P(論文) Some examples of the differences in flora and habitat of lichens between the Syowa Station area in the continental Antarctic, and a part of King George and Nelson Island (King George Island region) in the maritime Antarctic, are presented by the author who carried out the field surveys in both regions. A total of 57 species of lichens are enumerated for the Syowa Station area and 198 species for the King George Island region. Although most genera known to occur in the Syowa Station area are also found in the King George Island region, only 20 percent of the species occurring in the Syowa Station area are growing in the latter. Most lichens known from the Syowa Station area are microlichens, whereas in the King George Island region many macrolichens are growing beside microlichens. It might be most plausible to conclude that one of the factors influencing the rich lichen flora including many macrolichens in the maritime Antarctic is the mild weather conditions of the region. The major factor controlling lichens in the Antarctic appears to be not temperature but water supply. In the Syowa Station area extensive sites lack lichen cover, even where the ground is normally snow free in summer. On the other hand, both macro- and microlichens are growing everywhere in the King George Island region. Higher precipitation in the King George Island region dilutes the salinity brought by the wind-blown sea spray, while not so in the Syowa Station area because of the low precipitation in summer, though accurate meteorological data supporting this assumption are very few. departmental bulletin paper